Cholinesterase inhibitory potential of Dillenia suffruticosa chemical constituents and protective effect against Aβ−induced toxicity in transgenic Caenorhabditis elegans model - Saifullah Abubakar; Boon-Keat Khor; Kooi-Yeong Khaw; Vikneswaran Murugaiyah; Kit-Lam Chan (Elsevier, 2021)
Background: The Dillenia suffruticosa leaves have been used in African tribal herbal medicine to relieve inflammatory conditions and memory loss. However, little is known about the phytoconstituents and their potential against cholinergic dysfunction and β-amyloid accumulation related to neurodegenerative disorder. Purpose: Three triterpenoids and three flavonoids were isolated and investigated for acetylcholinesterase and butyrylcholinesterase inhibitions, including molecular docking mechanisms underlying the effects. The effect of the bioactive triterpenoids to delay the β-amyloid (Aβ)-induced paralysis of transgenic Caenorhabditis elegans strain GMC101 was also studied. Methodology: The extraction, fractionation, and isolation of the phytoconstituents from D. suffruticosa leaves followed the results of cholinesterase inhibitory activities determined using the modified Ellman's method. The in silico molecular docking simulation studies investigated the mode of interactions of the phytoconstituents on Torpedo californica acetylcholinesterase (TcAChE) and human butyrylcholinesterase (huBuChE) enzymes. The transgenic C. elegans strain GMC101 was tested with and without betulinic acid (1) or koetjapic acid (2) on their potential to delay paralysis. Results: Betulinic acid (1) had the highest potency in acetylcholinesterase inhibition (AChEI) and butyrylcholinesterase inhibition (BuChEI), followed by koetjapic acid (2), whereas stigmasterol glycoside (3) displayed the least potency. Vitexin (4), a C-glycoside displayed a higher potency than tiliroside (5), the O-glycosidic flavonoid against BuChE and AChE. Kaempferol (6), compared to its aglycone (5), was about 4 and 1.4 times more potent on AChEI and BuChEI, respectively. The selectivity indices suggested that the isolated phytoconstituents were dual AChE-BuChE inhibitors, more selective against BuChE than AChE, except 5. The molecular docking studies supported that small molecule like 6 only required very low binding energy unlike its glycoside (5), to dock fully at the overcrowded catalytic sites of AChE. Bulkier ligands docked more easily at lesser crowded BuChE active sites instead. For the first time, 2 was reported to delay Aβ-induced paralysis of transgenic C. elegans strain GMC101 and produced significantly longer survival time (p < 0.001) than 1. Conclusion: The studies demonstrated that bulky phytoconstituents from D. suffruticosa are more likely inhibitors of BuChE than AChE. Koetjapic acid (2) and betulinic acid (1) may possess protective potential against neurodegenerative disorders, related to their anti-cholinesterase and β-amyloid mechanisms.Significance statement:The bulkier phytoconstituents of D. suffruticosa are mainly triterpenoids and flavonoid glycosides which may have potential protective activity against memory loss and cognitive decline related to Alzheimer's disease.